Parietal scalp is another affected area in female pattern hair loss: An analysis of hair density and hair diameter - Salinee Rojhirunsakool (2019)
© 2018 Rojhirunsakool and Suchonwanit. Purpose: Female pattern hair loss (FPHL) is a common hair disease. However, studies of the quantitative measurement of FPHL are still limited. The aim of this study was to investigate the characteristics of hair density and hair diameter in normal women and FPHL patients, and further correlate the quantitative measurement with the clinical presentation of FPHL. Patients and methods: An evaluation of 471 FPHL patients and 236 normal women was carried out according to the Ludwig classification, and analysis was performed by using a computerized handheld USB camera with computer-assisted software. Various areas of the scalp, including frontal, parietal, midscalp, and occipital, were analyzed for hair density, non-vellus hair diameter, and percentage of miniaturized hair. Results: The hair density in normal women was the highest and the lowest in the midscalp and parietal areas, respectively. The FPHL group revealed the lowest hair density in the parietal area. Significant differences in hair density, non-vellus hair diameter, and percentage of miniaturized hair between the normal and FPHL groups were observed, especially in the midscalp and parietal areas. Conclusion: The parietal area is another important affected area in FPHL in addition to the midscalp area. This finding provides novel important information of FPHL and will be useful for hair transplant surgeons choosing the optimal donor sites for hair transplantation in women.